ANALYSIS AND RATING ASSESSMENT OF INFORMATIVENESS OF CLASSIFICATION CRITERIA OF AMERICAN COLLEGE OF RHEUMATOLOGY/EUROPEAN LEAGUE AGAINST RHEUMATISM 2010 IN THE EARLY DIAGNOSTICS OF RHEUMATOID ARTHRITIS - M.M. MADZHONOVA; K.O. SHARIFOV; F.M. KHAMIDOV; Y.U. SAIDOV; KH.R. MAKHMUDOV (Avicenna Tajik State Medical University, 2017)
Objective: To study and determine the rating significance of the main diagnostic positions of the classification criteria of the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR 2010) in the early diagnosis of rheumatoid arthritis (RA). Methods: 26 patients examined with a presumptive diagnosis of RA, who was diagnosed with the 2010 ACR/EULAR classification criteria at the first hospitalization, with a duration of «rheumatoid history» less than 12 months after the onset of symptoms of inflammatory joint damage. Results: Found that among the individual diagnostic positions, the classification criteria ACR/EULAR 2010, the highest rating in the verification of the diagnosis of «Early RA» have inflammatory lesions of a significant number (4-10) of small joints of hands and feet, as well as positive for to the rheumatoid factor and antibodies to the cyclic citrulled peptide. Conclusion: The obtained results testify to the high informativeness and sensitivity of the classification criteria ACR/EULAR 2010 in the verification of the diagnosis of RA in the debut stage of the disease.